Empowering Regional MSMEs through Clean Energy and Smart Technology in Thematic Villages - Kurnianingsih; Hendrawati, Dwiana; Lathief, Muttabik Fathul; Saddewisasi, Wyati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
This regional community service program seeks to empower Micro, Small, and Medium Enterprises (MSMEs) in the Semarang sub-districts of Meteseh and Tembalang by integrating clean energy solutions and smart technology. Meteseh faces significant challenges with plastic waste management, while Tembalang struggles with maintaining a stable energy supply for its MSMEs. To address these issues, the project introduced a solar-powered smart plastic waste shredding machine in Meteseh and a solar panel monitoring system in Tembalang. The shredding machine reduced unmanaged plastic waste by approximately 65%, enabling the processing of up to 15 kg of plastic per hour, while promoting recycling and environmental sustainability. In Tembalang, the solar energy system increased the operational hours of MSMEs’ craft production by 6–8 hours per day, resulting in a 100% increase in production capacity and a 30% reduction in operational energy costs. These initiatives have enhanced MSMEs’ productivity, sustainability, and resilience while fostering socio-cultural transformation and green economic awareness within the communities. The program demonstrates the measurable and transformative potential of clean energy and smart technology in regional development, offering a scalable and replicable model for sustainable economic growth across Indonesia and beyond.